Work-related injuries of rehabilitation therapists and measures for prevention - Wei Liu; Weibo Tian; Weibo Tian; Tianyu Wu; Bin Luo; Jiang Yi; Wenmao Li; Junjie Jiang; Yanlong Wei; Tianqi Zhang; Fengyue Zhang; Xiaoqin Duan; et al. (Frontiers Media S.A., 2024)
BackgroundRehabilitation therapists often perform physically demanding treatments that may result in work-related injuries, yet related studies are scarce. This study aimed to investigate the work-related injuries of rehabilitation therapists and provide feasible preventive measures.MethodsA cross-sectional study was carried out in 34 regions across China using an online questionnaire. The survey gathered responses primarily from 1,198 rehabilitative therapists working in 120 health institutes. Following data collection, descriptive analysis, chi-square tests, logistic regression, and receiver operating characteristic (ROC) curves were employed to analyze the data.ResultsIn this study, the incidence of work-related injuries was reported to be 87% (n = 1,041). The top three musculoskeletal issues reported were low back pain (12%), neck pain (10%), and shoulder pain (9%). Logistic regression and ROC curve analysis identified that working as a physiotherapist and years of work experience (OR [95% CI]: 1.03 [0.99-1.07]) were significant contributors to the incidence of work-related injuries. Specifically, neuro-physiotherapists (OR [95% CI]: 3.04 [1.56-5.92]), musculoskeletal physiotherapists (OR [95% CI]: 2.46 [1.16-5.18]), and intensive care physiotherapists (OR [95% CI]: 4.70 [1.24-17.88]) were at higher risk. Furthermore, five factors were proven to be associated with injury prevention as reported by therapists: patient engagement (OR [95% CI]: 0.38 [0.23-0.62]), improving techniques (OR [95% CI]: 0.59 [0.39-0.90]), maintaining exercise habits (OR [95% CI]: 0.59 [0.40-0.86]), utilizing instruments (OR [95% CI]: 0.80 [0.53-1.19]), and strengthening education (OR [95% CI]: 0.43 [0.21-0.90]).ConclusionThe present study investigated the factors contributing to work-related injuries among rehabilitation therapists, with a focus on identifying both risk and preventive measures. These findings offer new perspectives on decreasing injury risk.